Multi-functional mullite fiber-based porous ceramics with a multilevel pore structure assembled by alumina platelets and mullite whiskers. Issue 1 (1st January 2023) - Dong, Xue; Zheng, Yang; Xie, Dewei; Li, Dinghe
Abstract: Mullite fiber-based porous ceramics have been widely used in the field of heat insulation. To further broaden their applications in other fields, such as filtration and sound absorption, mullite whiskers and alumina platelets were introduced as the secondary structural materials in mullite fiber-based porous ceramics by a sol-gel combining heat-treating method, and new fiber-based porous ceramics with a unique multilevel pore structure were developed. By adjusting the molar ratios of aluminium tri-sec-butoxide to aluminium fluoride and calcination temperature, these fiber-based porous ceramics not only presented the characteristics of lightweight (maximum density of 0.38 g/cm 3 ) and good heat insulation (minimum thermal conductivity of 0.11 W/mK) comparable to traditional fiber-based porous ceramics, but also showed a superior specific surface area (up to 11.5 g/m 2 ) and excellent sound absorption performance (average sound absorption coefficient as high as 0.728). Owing to these outstanding characteristics, the corresponding porous ceramics are expected to be promising multifunctional materials in diverse fields, especially thermal insulation and sound absorption.